2013
DOI: 10.1155/2013/280810
|View full text |Cite
|
Sign up to set email alerts
|

Triterpene Esters and Biological Activities from Edible Fruits ofManilkara subsericea(Mart.) Dubard, Sapotaceae

Abstract: Manilkara subsericea (Mart.) Dubard (Sapotaceae) is popularly known in Brazil as “guracica.” Studies with Manilkara spp indicated the presence of triterpenes, saponins, and flavonoids. Several activities have been attributed to Manilkara spp such as antimicrobial, antiparasitic and antitumoral, which indicates the great biological potential of this genus. In all, 87.19% of the hexanic extract from fruits relative composition were evaluated, in which 72.81% were beta- and alpha-amyrin esters, suggesting that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 21 publications
1
25
0
2
Order By: Relevance
“…Literature search revealed that Compound 3 (phenol, dimethyl) [15] and Compound 6 (hexadecanoic acid, methyl ester) [15][16][17] have previously been reported with antibacterial activities. Meanwhile, a closely related derivative (hexadecanoic acid, ethyl ester), fractionated using ethanol from Brazilian M. subsericea, was reported with antibacterial activities in a separate study [18]. The bromo derivative of Compound 1 (butanoic acid, butyl ester) has also been tested with antibacterial activities [19].…”
Section: Discussionmentioning
confidence: 99%
“…Literature search revealed that Compound 3 (phenol, dimethyl) [15] and Compound 6 (hexadecanoic acid, methyl ester) [15][16][17] have previously been reported with antibacterial activities. Meanwhile, a closely related derivative (hexadecanoic acid, ethyl ester), fractionated using ethanol from Brazilian M. subsericea, was reported with antibacterial activities in a separate study [18]. The bromo derivative of Compound 1 (butanoic acid, butyl ester) has also been tested with antibacterial activities [19].…”
Section: Discussionmentioning
confidence: 99%
“…[ 23 ] This triterpene is structurally related to ursolic acid and was already found in the family Sapotaceae . [ 24 ] Considering the predominance of pentacyclic triterpenes in M. subsericea [ 25 26 ] and wide distribution of these substances through genus Manilkara ,[ 19 27 28 29 30 ] identification of pomolic acid contributes to the concept of chemotaxonomic significance of pentacyclictriterpenes in the genus Manilkara .…”
Section: Resultsmentioning
confidence: 99%
“…Dubard. 19,21 Whereas, the mass ion peaks at m/z 641.1713, corresponding to the suggested molecular formula C 28 19,21 Additionally, a compound at m/z 317.0653, corresponding to the suggested molecular formula C 16 H 12 O 7 was dereplicated as 3 0 -methoxy-4 0 ,5,7 trihydroxy avonol, which was formerly reported from the species Cuscuta reexa and was rst reported in the Manilkara genus. 22 Likewise, a avonoid-7-Oglycosides compound with the molecular formula C 28 H 32 O 14 was characterized as acacetin-7-O-rutinoside from the mass ion peak at m/z 593.1873 and was previously obtained from Origanum syriacum.…”
Section: Metabolic Prolingmentioning
confidence: 93%